Konsentrasi Kreatinin dan Urea dalam Darah Tikus Putih (Rattus norvegicus) Galur Wistar Akibat Pemberian Natrium Nitrit - Dyah Ayu Widyastuti; Maria Asih Ristianti; Ika Maya Sari (JURNAL ILMU KEFARMASIAN INDONESIA, 2019)
Sodium nitrite is one of common food addition in most meat product. This kind of food preservative is allowed by Permenkes No. 722/Menkes/Per/IX/88 only in minimum doses due to its carcinogenic effect. The most targeted organ is kidney which is sensitive to chemical matter as nefrotoxin. When the kidney is damaged, the erytropoietin secretion to form erytrocite is disturbed. Physiological damage in kidney can be identified by the concentration of blood creatinin and urea. The objective of this research is to study about blood creatinin and urea concentration of Wistar rats which is induced by sodium nitrite. Two groups of Wistar rats were induced by two doses of sodium nitrite (11.25 and 22.50 mg/kg body weight, respectively) a day with one group of control. Blood serum of those three groups were then be analyzed for creatinin and urea concentration each week for three months. The result showed that creatinin concertration is fluctuative during the day one to day ninety. The average of creatinin concentration for two treated groups is not significantly lower than control group. Generally, the urea concentration is increasing for day fourteen to seventy seven then decreasing in day eighty four to ninety. However, there are no significant differences among three groups.